Markets in the Light of Political-Economic Actors and Democracy.Reconsidering Conceptual Framework for Sustainability Politics (Global Journal of Human-Social Science, 2014)
Abstract not found
Keywords: political economy; political economic person; political economic organization; ideological orientation; mission; market models; positional analysis (P